Finishing systems on the carcass and meat characteristics and fatty acid profile of the longissimus thoracis muscle of Hereford steers in southern Brazil - Vanessa Peripolli; Grace Adele Gadotti; Carlos Eduardo Nogueira Martins; Betina Raquel Cunha dos Santos; Ivan Bianchi; Fabiana Moreira; Elizabeth Schwegler; Maiko Giorgi Philippe; Andressa Rozzetto Garcia; Marcílio Félix; José Laerte Nörnberg (Applied Food Research)
This study aimed to evaluate the effect of finishing systems on the carcass and meat characteristics and fatty acid profile of the longissimus thoracis (LT) muscle of Hereford steers in southern Brazil. Thirty-six carcasses were chosen from animals aged 18-24 months, weighing at least 220kg, with a minimum fat thickness of 3mm, finished on pasture (n=12), pasture with concentrate supplementation (n=12), and feedlot (n=12). Evaluated parameters included age, fat thickness, pH, color, marbling, and fatty acid composition. Correlations were found between meat color and pH (r=0.43), marbling and fat thickness (r=0.38), and age and fat color (r=0.98). The principal component analysis explained 52.52 % of the variation. Finishing systems significantly influenced carcass characteristics and meat color (P<0.05) but not pH or fat thickness (P>0.05) of Hereford steers. Chemical composition and fatty acid profile varied with the finishing system (P<0.05), except for total lipids and certain fatty acids (P>0.05). Pasture-finished Hereford steers exhibited distinct characteristics compared to feedlot-finished, with higher omega-3, C18:0, C18:1n9c, trans-11 C18:1n7, 18:3n3, CLA-18:2n7 cis-9 trans-11, EPA-C20:1n9, C20:4n6, C20:5n3, MUFA, and desirable fatty acids, along with darker meat and fat. Pasture-finished Hereford steer meats. Meat from pasture-finished Hereford steer selected based on premium-quality carcass and meat characteristics, reared under southern Brazilian conditions, shows potential to meet niche market demands.